Gibalne dejavnosti medicinskih sester v Sloveniji - Sima, Đurđa (Zdravstveno varstvo, 2002)
The article deals with physical activities of women. It defines the specifities of the profession of nurses and their recreation. The aim of the study is to determine on a sample, how many nurses practise physical activities and to present the positive influence of those acfivities on the quality of life. In the empirical part the shown results indicate that nurses in spite of demanding working time, their families and children practise physical activities in their spare time. The prevailing physical activities such as walking, trips and cycling show, that nurses practise such activifies that can include also their family members.
Keywords: Ankete; Exercise; gibalna aktivnost; Health behavior; kvaliteta življenja; Medicinske sestre; Nurses; Questionnaires; Sports; Šport; Telesna vaja; Zdrav način življenja; zdravo življenje